Education in Australia - Aland, Jenny (The Turkish Journal of Pediatrics, 1999)
School-based adoption of Multimedia: An Australian Perspective.This paper will look first at the work of Young Media Australia - a national community- based, information, research, training and advocacy organization working in the field of children, young people and mass media.The adoption rate of multi-media, including information technologies, in school systems across Australia will then be examined.Issues relating to the use of school-based multimedia, including the internet, will also be identified.